Analisis dan Perancangan Jaringan Local Area Network Pada Labolatorium Komputer SMA Negeri 1 Long Iram - Dedy Ariyadi; Sayekti Harits Suryawan (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
Computer networks have become one of the important needs for a school. now. Due to the transfer of the computer laboratory at SMA Negeri 1 Long Iram. In this project, the author wants to create a LAN-based network system (Local Area Network) with a star topology network model. to achieve the target of preparing for ANBK (Computer-Based National Assessment) at the high school. This project uses stage methods, namely problem identification, site observation, data collection, system analysis, system design and testing stages. The purpose of the project is to meet the needs of school facilities in the form of LAN networks that will be used for ANBK and Minimum Competency Assessment and Character Survey so that schools can successfully follow the agenda. The result of the project made is a LAN (Local Area Network) network system with a star topology network model successfully running smoothly as evidenced by the ANBK simulation a week before the implementation of ANBK itself. The benefits of this project are so that schools can participate in ANBK activities and Minimum Competency Assessment and Character Survey, and can maximize the learning process with technology facilities in the computer laboratory.